Socio-legal systems and implementation of the Nash solution in Debreu-Hurwicz equilibrium - Claus-Jochen Haake; Walter Trockel (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
In this article we combine Debreu's (1952) social system with Hurwicz's (1994, 2008) ideas of embedding a "desired" game form into a "natural" game form that includes all feasible behavior, even if it is "illegal" according to the desired form. For the resulting socio-legal system we extend Debreu's concepts of a social system and its social equilibria to a socio-legal system with its Debreu-Hurwicz equilibria.We build on a more general version of social equilibrium due to Shafer and Sonnenschein (1975) that also generalizes the dcmechanism of Koray and Yildiz (2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash's demand game an implementation of the Nash bargaining solution in Debreu-Hurwicz equilibrium.
urn:nbn:de:0070-pub-29536013
Keywords: D02; C78; C72; 330; socio-legal systems; implementation; social systems; generalized games; Nash demand game